PERKEMBANGAN DESA WISATA DI KABUPATEN BADUNG (Studi Kasus Desa Wisata Baha) - Samiarta, I Gede; Mahagangga, I Gst. Agung Oka (JURNAL DESTINASI PARIWISATA; Vol 4 No 2 (2016): VOL 4, NO 2 (2016): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATA, 2016)
This research titled Tourism Village Development in Badung Regency (Case Study in Baha Tourism Village). The purpose of this research is to find out of the tourism development in Baha Village since this village is disignated as tourism village in Badung. The data are collected by observation, indeepth interview and literatur study. The obtained data were analyzed in qualitative data analysis. The results of this study after being analyzed using tourism area life cycle theory that the development of Baha Tourism Village is in involvement phase where the people who have taken initiative to providing the tourist atraction service and the tourism fasilities in Baha tourism village. Beside of that in it cooperation between the people and goverment is try to make the promotion tools like website. This aims is to facilitate the tourists to get information about tourist village of Baha. From this development has also spawned the tourism organizations with the name of “Kelompok sadar Wisata” or commonly abbreviated to be “POKDARWIS”
Keywords: Development, Tourism Village, Badung Regency